ChemInform Abstract: A Highly Efficient Gold‐Catalyzed Photoredox α‐C(sp3)—H Alkynylation of Tertiary Aliphatic Amines with Sunlight. Issue 36 (September 2015) - Xie, Jin; Shi, Shuai; Zhang, Tuo; Mehrkens, Nina; Rudolph, Matthias; Hashmi, A. Stephen K.
Abstract The title radical process is optimized to allow mild reaction conditions in the presence of [Au(μ‐dppm)2](OTf)2 as the catalyst.